Perceptions of Individuals with Parkinson's Disease about Quality of Life (2018)
Introduction: Parkinson's disease is a neurodegenerative disorder manifested by motor and non-motor symptoms that compromise patients' quality of life. The instrument used to assess Parkinson's disease patients' quality of life is the Parkinson's Disease Questionnaire (pdq-39). This study aims to identify issues related to quality of life from the patients' perspective, compare the results obtained with the aspects included in the pdq-39, and describe some strategies that patients have adopted to overcome difficulties. Materials and methods: This is a qualitative and descriptive study based on a focus group consisting of six patients. Data were analyzed using the content analysis method. Results: Aspects related to all pdq-39 domains were mentioned by the patients, highlighting those related to limitations on their mobility and daily activities, as well as aspects related to their emotional wellbeing. The patients did not mention some aspects of mobility that are included in the pdq-39, but limitations in the domain of emotional well-being that are included in the pdq-39 were detected. In order to overcome difficulties, patients devise various strategies that require social support. Conclusion: Understanding and reflecting on Parkinson's disease patients' perceptions of their quality of life contributes to our understanding of the disease and stimulates proposals for adequate clinical interventions to provide comprehensive care. It is suggested that the pdq-39 be reviewed and adapted to the current context, taking into account the most recent knowledge and technological advances related to Parkinson's disease.